2014
DOI: 10.1016/j.bbalip.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cholesterol transporters and modulation of hepatic lipid metabolism: Implications for diabetic dyslipidaemia and steatosis

Abstract: Targeting StarD3 may increase circulating levels of HDL and protect the liver against lipotoxicity; loss of hepatic expression of this protein, induced by genetic obesity, may contribute to the pathogenesis of dyslipidaemia and steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Cholesterol is an important precursor metabolite with roles in energy metabolism through induction of oxidative stress and other metabolic alterations . Several mitochondrial transport processes can be affected by alterations in cholesterol synthesis . STARD3 is a cholesterol transporter that mediates trafficking of cholesterol to the endoplasmic reticulum, mitochondrial, and plasma membrane .…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is an important precursor metabolite with roles in energy metabolism through induction of oxidative stress and other metabolic alterations . Several mitochondrial transport processes can be affected by alterations in cholesterol synthesis . STARD3 is a cholesterol transporter that mediates trafficking of cholesterol to the endoplasmic reticulum, mitochondrial, and plasma membrane .…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis administration also seemed to affect glucose metabolism by increasing the expression of G6pc. G6pc positively regulates gluconeogenesis and can increase blood glucose levels [30]. …”
Section: Discussionmentioning
confidence: 99%
“…The START domain of 54kDa endosomal StarD3 (MLN64) is an helix grip fold, providing a hydrophobic binding site for one molecule of cholesterol, facilitating cholesterol trafficking to the endoplasmic reticulum (ER), mitochondria and plasma membrane (Charman et al, 2010; Alpy et al, 2013; van der Kant et al, 2013). Our previous work demonstrated regulation of StarD3 expression by lipid-responsive transcription factors and macrophage sterol content (Borthwick et al 2009) and repression by genetic obesity in hepatic tissues (Soffientini et al, 2014), while overexpression of STARD3 in macrophages enhanced expression of ABCA1 and cholesterol efflux to apoA-I (Borthwick et al, 2010). …”
mentioning
confidence: 98%
“…This was a surprising outcome, as expression of STARD3 was clearly sterol-dependent in human THP-1 macrophages (Borthwick et al, 2009) and repressed by genetic obesity in both male and female fa/fa rats (Soffientini et al, 2014). The promoter regions of both rat and human StarD3/STARD3 contain putative binding sites for lipid responsive transcription factors, such as peroxisome proliferator activated receptors, retinoid X receptors and SREBPs (Borthwick et al, 2009), while the marked increases in cholesterol biosynthesis observed in response to cholesterol depletion (Table 1) suggest that SREBP-dependent induction of HMG CoA reductase is operating correctly.…”
mentioning
confidence: 99%
See 1 more Smart Citation